2019
DOI: 10.18632/oncotarget.27301
|View full text |Cite
|
Sign up to set email alerts
|

Pre-surgical connectome features predict IDH status in diffuse gliomas

Abstract: BackgroundGliomas are the most common type of malignant brain tumor. Clinical outcomes depend on many factors including tumor molecular characteristics. Mutation of the isocitrate dehydrogenase (IDH) gene confers significant benefits in terms of survival and quality of life. Preoperative determination of IDH genotype can facilitate surgical planning, allow for novel clinical trial designs, and assist clinical counseling surrounding the individual patient’s disease.MethodsIn this study, we aimed to evaluate a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…With respect to molecular classification in terms of IDH mutation status, Suchorska et al stratified 301 patients with WHO grade II (n = 181) or grade III glioma (n = 120) according to their molecular profile and reviewed pre-operative MRI and volumetric analyses of contrast-enhanced and T2 volumes, showing that contrast enhancement on initial MRI is a prognostic factor for survival with dependence on volume distinguishing IDH-mutated from IDH-wild type tumors (51). Similarly, with an eye towards predicting IDH mutation pre-operatively, several publications have employed MRI and ML (57,58,61). Zhang et al employed preoperative MRIs of 120 HGG patients with confirmed IDH genotype, to extract 2970 imaging features from pre-and post-contrast T1-weighted, T2-weighted, and apparent diffusion coefficient (ADC) maps.…”
Section: Imaging and Tumor Grading-based Survival Predictionmentioning
confidence: 99%
“…With respect to molecular classification in terms of IDH mutation status, Suchorska et al stratified 301 patients with WHO grade II (n = 181) or grade III glioma (n = 120) according to their molecular profile and reviewed pre-operative MRI and volumetric analyses of contrast-enhanced and T2 volumes, showing that contrast enhancement on initial MRI is a prognostic factor for survival with dependence on volume distinguishing IDH-mutated from IDH-wild type tumors (51). Similarly, with an eye towards predicting IDH mutation pre-operatively, several publications have employed MRI and ML (57,58,61). Zhang et al employed preoperative MRIs of 120 HGG patients with confirmed IDH genotype, to extract 2970 imaging features from pre-and post-contrast T1-weighted, T2-weighted, and apparent diffusion coefficient (ADC) maps.…”
Section: Imaging and Tumor Grading-based Survival Predictionmentioning
confidence: 99%
“…IDH gene-mutant tumors demonstrated significiantly good clinical outcomes as compared with the wild types. IDH mutation has been recognized to be of central prognostic and biologic importance, and the diagnostic tool has been incorporated in the diagnosis since 2016 (18,30). Notably, IDH gene status has been made a major criterion for tumor classification (1,25,39).…”
Section: Discussionmentioning
confidence: 99%
“…While surgical treatment is currently the main treatment for patients with glioma, there are certain risks in the operation. The traction and stress reaction of related brain tissue during surgery can cause complications such as cerebral edema, which in turn affects the prognosis of patients (12,13). Postoperative cognitive dysfunction (POCD) refers to the slight damage to the brain's advanced cortical function after anesthesia and surgery, which affects the patient's memory, attention and information processing capabilities, and is a mild neurocognitive disorder.…”
Section: Discussionmentioning
confidence: 99%